Analysis of Supervision Punishment in the National Criminal Code as an Instrument of Modern Sentencing in Indonesia - Fitri Sulis Setiyowati; Hery Chariansyah (Jurnal Kewarganegaraan, 2026)
Supervision punishment is one of the significant innovations introduced by Law Number 1 of 2023 concerning the Indonesian Criminal Code. Its formulation reflects a shift in Indonesia’s sentencing policy from imprisonment-oriented punishment toward a more proportional, corrective, rehabilitative, and community-based model. This article examines two main issues: the concept of supervision punishment under the National Criminal Code and its prospects in realizing modern sentencing objectives in Indonesia. This study employs normative legal research using statutory, conceptual, and limited comparative approaches. The findings indicate that supervision punishment should not be understood merely as a lenient sanction but as a principal punishment that embodies the principles of individualized sentencing and offender rehabilitation outside correctional institutions. Prospectively, supervision punishment may serve as an important instrument to reduce the harmful effects of short-term imprisonment, strengthen rehabilitation, and support restorative justice. However, its effectiveness depends on implementing regulations, sentencing guidelines, the institutional capacity of probation officers, coordination among criminal justice agencies, and a shift in legal culture from prison-oriented sentencing to community-based sentencing.